2017
DOI: 10.1111/trf.14440
|View full text |Cite
|
Sign up to set email alerts
|

Blood use in hematologic malignancies: a nationwide overview in Sweden between 2000 and 2010

Abstract: Results from this population-based overview of blood use in hematologic malignancies showed high variability depending on diagnosis and age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
0
12
1
Order By: Relevance
“…Over two‐thirds of the MDS patients require more than one RBC transfusion over the course of the disease . Considering the clinical significance of transfusion intensity, which was recently demonstrated, the negative impact on health‐related quality of life and that the direct costs of transfusions are substantial, it is important to optimize transfusion therapy to these patients.…”
Section: Methodsmentioning
confidence: 99%
“…Over two‐thirds of the MDS patients require more than one RBC transfusion over the course of the disease . Considering the clinical significance of transfusion intensity, which was recently demonstrated, the negative impact on health‐related quality of life and that the direct costs of transfusions are substantial, it is important to optimize transfusion therapy to these patients.…”
Section: Methodsmentioning
confidence: 99%
“…Zhao et al . reported that the median number of transfused RBC units was zero for their cohort, with an average of 7·5 units . Our study had greater variation in the duration of follow‐up compared to the Swedish study, or 1 month‐14 years compared to 2·6–7·3 years.…”
Section: Discussionmentioning
confidence: 61%
“…In our cohort of CLL patients, one‐third required RBC transfusions during the course of the study compared to 44% of CLL patients in the study by Zhao et al . of 5253 Swedish CLL patients . The median number of transfused RBC units in our study was six for the transfused subgroup and zero for the whole cohort.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations